Method for improving wear resistance of 60NiTi alloy by using high-power pulse magnetron sputtering DLC film layer

CN118326351BActive Publication Date: 2026-10-27HARBIN INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410480928.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2026-10-27
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

然而,气相沉积法容易造成薄膜与基体晶格得不匹配,会出现残余应力较大情况,导致膜层脱落

Benefits of technology

[0007]有鉴于此,本发明目的在于提供一种利用高功率脉冲磁控溅射DLC膜层提高60NiTi合金耐磨性的方法。本发明采用高功率脉冲磁控溅射DLC膜层的方式,能够有效降低60NiTi合金的摩擦系数,提高60NiTi合金的硬度,且膜层与60NiTi合金具有良好的结合强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326351B_ABST
    Figure CN118326351B_ABST
Patent Text Reader

Abstract

The application provides a method for improving wear resistance of 60NiTi alloy by using high-power pulse magnetron sputtering DLC film layer, and belongs to the technical field of alloy surface treatment. Ti is used as a target material, and a Ti transition layer is obtained by first high-power pulse magnetron sputtering. Mixed gas of ethylene and high-purity argon is used as gas for second high-power pulse magnetron sputtering, wherein the argon is responsible for providing high-energy ions to generate plasma, and the ethylene is used as a carbon source of the DLC film layer and provides hydrogen elements. Under the action of the high-power pulse magnetron sputtering, the smooth and dense DLC film is deposited, the friction coefficient of the 60NiTi alloy can be effectively reduced, the hardness of the 60NiTi alloy can be improved, and the 60NiTi alloy can be used as a new type of bearing material with low friction coefficient and high hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy surface treatment technology, and in particular to a method for improving the wear resistance of 60NiTi alloy by using high-power pulsed magnetron sputtering of DLC film. Background Technology

[0002] Bearings are crucial components in mechanical equipment. Their main functions are to transmit loads, support rotating mechanical parts, ensure rotational accuracy, and reduce the coefficient of friction between mechanical components. They have important applications in aerospace, energy and transportation, and instrumentation. Currently, the most commonly used bearing material is the second-generation bearing steel M50, which has high hardness and good tribological properties. However, its poor corrosion resistance and strong magnetism limit its application in the aerospace field.

[0003] 60NiTi alloy (Ni mass fraction 60%) is characterized by its high hardness, low elastic modulus, non-magnetic properties, low density, good wear resistance, and corrosion resistance. The alloy contains a parent phase TiNi and nanoscale reinforcing phases Ni4Ti3 and Ni3Ti. The presence of these reinforcing phases is the reason for the high hardness and good wear resistance of the 60NiTi alloy, making it a popular choice for novel aerospace bearings. Ideally, aerospace bearing materials should have a high surface hardness and low coefficient of friction, while the core possesses a certain degree of toughness. This allows the bearing to alleviate stress during operation, extending its service life and meeting the required service duration in aircraft or spacecraft, avoiding secondary replacements and saving manpower and resources. Therefore, surface treatment of bearings is particularly important.

[0004] Currently, surface modification methods for bearing materials mainly include surface deformation strengthening, chemical heat treatment, and vapor deposition of hard and wear-resistant layers. Surface deformation strengthening involves using external force to induce plastic deformation on the metal surface, increasing the dislocation density within the material. The interaction between dislocations prevents lattice deformation, thereby improving the hardness and fatigue strength of bearing parts. Its advantage is that the strengthened layer is thick, reaching millimeter levels. However, it can easily cause overcooling hardening and brittleness in thin-walled bearings, and also increases the surface roughness of bearing parts.

[0005] Chemical heat treatment strengthening mainly refers to the diffusion of atoms into the material surface in a specific atmosphere, forming a diffusion layer that strengthens the surface. This is typically a carburizing or nitriding process. In this process, gases containing these two elements are introduced into a heat treatment furnace at high temperature. The gases then decompose into active atoms that are adsorbed onto the bearing surface and diffuse into the bearing interior, forming a carburized or nitrided layer of a certain thickness, thus extending the bearing's service life. While heat treatment can improve the hardness, strength, and toughness of materials, it can also negatively impact their overall properties.

[0006] Vapor deposition methods are divided into two categories: physical vapor deposition and chemical vapor deposition. However, vapor deposition methods are prone to causing lattice mismatch between the thin film and the substrate, resulting in large residual stress and film delamination. Summary of the Invention

[0007] In view of this, the purpose of this invention is to provide a method for improving the wear resistance of 60NiTi alloy by using high-power pulsed magnetron sputtering of DLC films. This invention employs high-power pulsed magnetron sputtering of DLC films, which can effectively reduce the friction coefficient of 60NiTi alloy, increase its hardness, and achieve good bonding strength between the film and the 60NiTi alloy.

[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0009] This invention provides a method for improving the wear resistance of 60NiTi alloy by using high-power pulsed magnetron sputtering of DLC films, comprising the following steps:

[0010] Using Ti as the target material, a first high-power pulsed magnetron sputtering was performed on the surface of a 60NiTi substrate to obtain a 60NiTi substrate with a deposited Ti transition layer.

[0011] A second high-power pulsed magnetron sputtering was performed on the surface of the 60NiTi substrate with a deposited Ti transition layer using a mixed gas of ethylene and high-purity argon as the working gas, to form a DLC film on the surface of the Ti transition layer.

[0012] Preferably, before the first high-power pulsed magnetron sputtering, the 60NiTi substrate is further subjected to pretreatment, which includes the following steps:

[0013] The 60NiTi substrate was ground, polished, and cleaned.

[0014] Preferably, the first high-power pulsed magnetron sputtering is performed in an argon atmosphere.

[0015] Preferably, the parameters of the first high-power pulsed magnetron sputtering include:

[0016] The working air pressure is 0.6–0.8 Pa;

[0017] Set the frequency to 400-600Hz;

[0018] The pulse width is 50–115 μs;

[0019] The power is 150-200W;

[0020] The working time is 10 to 15 minutes.

[0021] Preferably, the thickness of the Ti transition layer is 0.2 to 0.5 μm.

[0022] Preferably, during the second high-power pulsed magnetron sputtering, the argon flow rate is 90-100 ccm and the ethylene flow rate is 1.5-2.5 sccm.

[0023] Preferably, the parameters of the second high-power pulsed magnetron sputtering include:

[0024] The working air pressure is 0.6–0.8 Pa;

[0025] The operating frequency is 500–700 Hz;

[0026] Sputtering power is 100–200W;

[0027] The target-base distance is 10–15 cm;

[0028] The working time is 50 to 60 minutes.

[0029] Preferably, during the second high-power pulsed magnetron sputtering, the 60NiTi substrate with the deposited Ti transition layer is fixed at the center of the sample stage and maintains its rotation.

[0030] Preferably, the total thickness of the Ti transition layer and the DLC film is 1.2 to 1.7 μm.

[0031] This invention provides a 60NiTi alloy-DLC film composite material, which is obtained by processing a 60NiTi substrate using the above method; the 60NiTi alloy-DLC film composite material includes a 60NiTi substrate, a Ti transition layer located on the surface of the 60NiTi substrate, and a DLC film layer located on the surface of the Ti transition layer.

[0032] This invention provides a method for improving the wear resistance of 60NiTi alloy using high-power pulsed magnetron sputtering of a DLC film, comprising the following steps: using Ti as the target material, performing a first high-power pulsed magnetron sputtering on the surface of a 60NiTi substrate to obtain a 60NiTi substrate with a deposited Ti transition layer; using a mixed gas of ethylene and high-purity argon as the working gas, performing a second high-power pulsed magnetron sputtering on the surface of the 60NiTi substrate with the deposited Ti transition layer to form a DLC film on the surface of the Ti transition layer. Diamond-like carbon (DLC) films possess high hardness and a low coefficient of friction, making them excellent friction-reducing and wear-resistant coating materials. The high hardness and high strength of the 60NiTi alloy can provide a good supporting substrate for the DLC film. This invention utilizes high-power pulsed magnetron sputtering technology to deposit a smooth and dense DLC film on the surface of the 60NiTi alloy. Specifically, this invention uses Ti as the target material and obtains a Ti transition layer through a first high-power pulsed magnetron sputtering. The internal stress and bonding strength of a thin film determine its stability and service life. DLC films deposited directly on the substrate generally have low film / substrate bonding strength and high internal stress, making them prone to cracking, wrinkling, and even detachment during application. A Ti transition layer can reduce abrupt changes in interfacial physical properties, eliminate internal stress caused by material differences between the coating and the substrate, and improve the bonding strength between the DLC film and the substrate. Simultaneously, it improves the mismatch in thermal expansion coefficients between the film and the substrate, effectively coordinating the plastic deformation of the substrate under load. This invention uses a mixture of ethylene (C2H2) and high-purity argon (Ar) as the gas for the second high-power pulsed magnetron sputtering. Argon provides high-energy ions to generate plasma, while ethylene serves as the carbon source for the DLC film and provides hydrogen. Under the action of high-power pulsed magnetron sputtering, a smooth and dense DLC film is deposited, which can effectively reduce the friction coefficient of 60NiTi alloy and increase its hardness, making it a novel bearing material with low friction coefficient and high hardness.

[0033] Furthermore, this application improves the performance of the 60NiTi alloy-DLC film composite material by controlling the parameters of high-power pulsed magnetron sputtering. The results of the embodiments show that the friction coefficient of the 60NiTi alloy surface after high-power pulsed magnetron sputtering of the DLC film is approximately 0.2, the hardness is 6.01–7.18 GPa, the elastic modulus is 49.4–55.94 GPa, and the H / E ratio is between 0.121 and 0.130. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the structure of a high-power pulse sputtering furnace;

[0035] Figure 2Image of the finished 60NiTi alloy-DLC film composite material;

[0036] Figure 3 Raman spectra of DLC films prepared at different powers;

[0037] Figure 4 Hardness and elastic modulus of DLC films prepared for different power levels;

[0038] Figure 5 Comparison of friction coefficients between DLC films prepared at different power levels and 60NiTi. Detailed Implementation

[0039] This invention provides a method for improving the wear resistance of 60NiTi alloy by using high-power pulsed magnetron sputtering of DLC films, comprising the following steps:

[0040] Using Ti as the target material, a first high-power pulsed magnetron sputtering was performed on the surface of a 60NiTi substrate to obtain a 60NiTi substrate with a deposited Ti transition layer.

[0041] A second high-power pulsed magnetron sputtering was performed on the surface of the 60NiTi substrate with a deposited Ti transition layer using a mixed gas of ethylene and high-purity argon as the working gas, to form a DLC film on the surface of the Ti transition layer.

[0042] This invention uses Ti as the target material and performs a first high-power pulsed magnetron sputtering on the surface of a 60NiTi substrate to obtain a 60NiTi substrate with a deposited Ti transition layer. This invention does not have specific requirements regarding the source of the 60NiTi substrate; commercially available 60NiTi substrates or self-prepared substrates are both acceptable. When self-prepared, the preferred method for preparing the 60NiTi substrate includes the following steps:

[0043] Nickel and titanium raw materials were vacuum melted and stirred to obtain 60NiTi metal ingots;

[0044] The 60NiTi metal ingot is cut to obtain a 60NiTi substrate.

[0045] In this invention, the preferred mass ratio of nickel raw material to titanium raw material is 6:4.

[0046] In this invention, the vacuum melting process is preferably performed 6 times. In this invention, the stirring melting process is preferably performed using magnetic stirring, and the stirring melting process is preferably performed 2 times.

[0047] In this invention, the thickness of the 60NiTi substrate is preferably 1-2 mm. This invention does not impose special requirements on the shape and specific dimensions of the 60NiTi substrate; the design can be tailored to the actual application. As a specific embodiment of this invention, the shape of the 60NiTi substrate is preferably circular or triangular, and the diameter is preferably 30 mm.

[0048] In this invention, before the first high-power pulsed magnetron sputtering, a pretreatment of the 60NiTi substrate is further included, and the pretreatment preferably includes the following steps:

[0049] The 60NiTi substrate was ground, polished, and cleaned.

[0050] In this invention, the polishing is preferably done by sequentially polishing with 200 to 5000# sandpaper until the surface is smooth and no obvious scratches are visible.

[0051] In this invention, the polishing is preferably performed on a metallographic polishing machine using a diamond polishing agent, followed by water polishing, until no pits or fine scratches are visible under an optical microscope.

[0052] In this invention, the cleaning is preferably performed by ultrasonic cleaning with anhydrous ethanol for 10 minutes in an ultrasonic cleaner, followed by drying.

[0053] In this invention, the first high-power pulsed magnetron sputtering and the second magnetron sputtering are preferably performed in a high-power pulsed sputtering furnace, which mainly includes a furnace body, a vacuum system, a sample holder, a target holder, a gas supply system, a cooling system, and a high-power pulsed power supply.

[0054] In this invention, the first high-power pulsed magnetron sputtering is preferably performed in an argon atmosphere. In this invention, the argon gas is preferably high-purity argon gas, and the purity of the high-purity argon gas is preferably ≥99.999%. In this invention, the preferred method for providing the argon atmosphere is:

[0055] The 60NiTi substrate was transferred to the sample holder of the high-power pulsed sputtering furnace. The furnace door was closed, and the pressure inside the vacuum chamber was evacuated to 5 × 10⁻⁶ using a mechanical pump and a molecular pump. -3 Below Pa, high-purity argon gas is introduced into the vacuum chamber, and the gas pressure inside the vacuum chamber is controlled by a gate valve. The working gas pressure is adjusted to 0.6-0.8 Pa.

[0056] In this invention, the parameters of the first high-power pulsed magnetron sputtering preferably include:

[0057] The working air pressure is preferably 0.6 to 0.8 Pa, more preferably 0.7 to 0.8 Pa;

[0058] The preferred frequency setting is 400-600Hz, and more preferably 500Hz;

[0059] The pulse width is preferably 50–115 μs, more preferably 70–90 μs;

[0060] The power is preferably 150-200W, more preferably 180-200W;

[0061] The working time is preferably 10 to 15 minutes, and more preferably 12 to 15 minutes.

[0062] In this invention, the thickness of the Ti transition layer is preferably 0.2 to 0.5 μm, more preferably 0.3 to 0.4 μm.

[0063] After obtaining a 60NiTi substrate with a deposited Ti transition layer, this invention uses a mixture of ethylene and high-purity argon as the working gas to perform a second high-power pulsed magnetron sputtering on the surface of the 60NiTi substrate with the deposited Ti transition layer, thereby obtaining a 60NiTi alloy-DLC film composite material. In this invention, during the second high-power pulsed magnetron sputtering, the argon flow rate is preferably 90–100 ccm, more preferably 98 ccm; the ethylene flow rate is preferably 1.5–2.5 sccm, more preferably 2 sccm.

[0064] In this invention, the parameters of the second high-power pulsed magnetron sputtering preferably include:

[0065] The working air pressure is preferably 0.6 to 0.8 Pa, more preferably 0.6 to 0.7 Pa;

[0066] The operating frequency is preferably 500-700Hz, and more preferably 600Hz;

[0067] The sputtering power is preferably 100-200W, more preferably 150W;

[0068] The target-base distance is preferably 10-15 cm, more preferably 12-15 cm;

[0069] The working time is preferably 50 to 60 minutes, and more preferably 55 to 60 minutes.

[0070] In this invention, during the second high-power pulsed magnetron sputtering, the 60NiTi substrate with the deposited Ti transition layer is fixed at the center of the sample stage and keeps rotating to ensure the uniformity of the coating deposition process.

[0071] In this invention, the total thickness of the Ti transition layer and the DLC film is preferably 1.2 to 1.7 μm, more preferably 1.4 to 1.6 μm.

[0072] This invention provides a 60NiTi alloy-DLC film composite material, which is obtained by processing a 60NiTi substrate using the above method; the 60NiTi alloy-DLC film composite material includes a 60NiTi substrate, a Ti transition layer located on the surface of the 60NiTi substrate, and a DLC film layer located on the surface of the Ti transition layer.

[0073] The following detailed description, in conjunction with embodiments, illustrates the method provided by the present invention for improving the wear resistance of 60NiTi alloy using high-power pulsed magnetron sputtering DLC ​​film, but these descriptions should not be construed as limiting the scope of protection of the present invention.

[0074] The high-power pulse sputtering furnace used in the following embodiments was independently developed by the State Key Laboratory of Welding at Harbin Institute of Technology. The equipment mainly includes a furnace body, vacuum system, sample holder, target holder, gas inlet system, cooling system, and high-power pulse power supply. A schematic diagram is shown below. Figure 1 As shown.

[0075] Example 1

[0076] (1) Preparation of 60NiTi substrate

[0077] 1) Cut the raw nickel block into small pieces of 2mm×2mm×2mm, and use a grinding wheel to treat the surface to remove the oxide layer and stains;

[0078] 2) Cut the titanium mesh into a cross shape with a length and width of 2cm, and remove the surface oxide film by acid pickling;

[0079] 3) The mass ratio of nickel block to titanium mesh is 6:4. The weighed nickel and titanium are repeatedly melted in a vacuum melting furnace six times, and magnetic stirring is turned on twice to obtain 60NiTi metal ingots.

[0080] 4) The prepared metal ingot is cut into circular pieces with a diameter of 30 mm and a thickness of 1 mm and triangular 60NiTi substrate thin sheets for subsequent experiments and tests.

[0081] (2) High-power pulsed magnetron sputtering of DLC film layers

[0082] 1) Polish the 60NiTi substrate with 200-5000# sandpaper until the surface is smooth and no obvious scratches are visible;

[0083] 2) Polish with diamond polishing compound on a metallographic polishing machine, then water polish until there are no pits or fine scratches under an optical microscope. Then ultrasonically clean with anhydrous ethanol for 10 minutes in an ultrasonic cleaner and dry with a hair dryer.

[0084] 3) Load the 60NiTi substrate onto the rotating frame and close the furnace door;

[0085] 4) Use mechanical pumps and molecular pumps to evacuate the air pressure in the vacuum chamber to 5 × 10⁻⁶. -3 Below Pa;

[0086] 5) Introduce high-purity argon into the vacuum chamber, control the gas pressure inside the vacuum chamber using a gate valve, adjust the working gas pressure to 0.8 Pa, set the frequency to 500 Hz, pulse width to 70 μs, power to 200 W, start the high-power pulsed magnetron sputtering power supply, and work for 15 min to deposit a Ti transition layer on the 60NiTi substrate. After the transition layer deposition is completed, turn off the magnetron sputtering power supply.

[0087] 6) Open the C2H2 inlet valve, adjust the argon flow rate to 98ccm, the ethylene flow rate to 2sccm, the working pressure to 0.6Pa, the working frequency to 500~700Hz, the sputtering power to 100W, and the target-substrate distance to 15cm. Then start the sample stage rotation frame so that the sample stage is located at the perpendicular bisector of the line connecting the centers of the two targets and keeps rotating.

[0088] 7) Then, the high-power pulsed magnetron sputtering power supply was started, and the deposition time was set to 60 min. Finally, a DLC film was deposited on the surface of the 60NiTi substrate to obtain the 60NiTi alloy-DLC film composite material.

[0089] The finished product image of the 60NiTi alloy-DLC film composite material is shown below. Figure 2 As shown. Figure 2 In the diagram, the black portion represents the DLC film, and the metallic-luster portion represents the equipment clamping part, which has no DLC film on its surface. It can be seen that the method of this invention can deposit a DLC film layer on the surface of 60NiTi alloy, and the film quality is good with no obvious cracks.

[0090] Example 2

[0091] Compared with Example 1, the sputtering power in step 6) is 150W.

[0092] Example 3

[0093] Compared with Example 1, the sputtering power in step 6) is 200W.

[0094] Raman spectra of DLC films prepared by pulsed magnetron sputtering under different power conditions after Gaussian function fitting are shown below. Figure 3 As shown in the figure, it can be seen that the fitted G peak position in the Raman spectra of samples with different powers is all around 1520 cm⁻¹. -1 Nearby, according to literature reports, the G peak is located at 1600 cm. -1 Up to 1510cm -1At this stage, the diamond-like carbon (DLC) film is in the transition phase from nanocrystalline graphite to amorphous carbon. A smaller ID / IG ratio indicates a higher proportion of sp3 in the material. The samples at 100W, 150W, and 200W have surface carbon films that are roughly at the end of the second stage, with the surface being primarily amorphous carbon. The integrated intensity ratios of the peak and the G peak (ID / IG) are 0.55, 0.79, and 0.88, respectively, indicating that the proportion of sp3 in the DLC film gradually decreases with increasing pulsed magnetron sputtering power.

[0095] Test Example 1

[0096] The nanoindentation hardness and elastic modulus of the DLC films obtained in Examples 1-3 were tested. The nanoindentation hardness and elastic modulus data of the obtained DLC films are as follows: Figure 4 As shown in the figure, the hardness of the obtained DLC film gradually decreases with the increase of power. The DLC film prepared with a power of 100W has the highest hardness, reaching 7.18GPa. The DLC film prepared with a power of 200W has the second highest hardness, at 6.01GPa. The DLC film prepared with a power of 150W has the lowest hardness, at 6.41GPa.

[0097] The change in elastic modulus of the DLC film is consistent with the change in hardness, with the elastic modulus gradually decreasing as the pulse power increases. The difference in hardness and elastic modulus is mainly due to the different proportions of sp3 in the DLC film; the higher the proportion of sp3 hybridization, the higher the hardness and modulus values ​​of the film. For bearing materials, many scholars have found that hardness alone cannot be used to evaluate them; elastic modulus also contributes to the wear resistance of bearings. The ratio of hardness to elastic modulus, H / E, is a key indicator; the higher the value, the better the wear resistance. The H / E of the three samples ranged from 0.12 to 0.13, with the highest H / E and the best overall performance observed at an impact power of 150W.

[0098] Test Example 2

[0099] The wear resistance of the DLC films obtained in Examples 1-3 was tested. Measurements were taken using a high-temperature tribological testing machine with silicon nitride as the friction material, a load of 150 N, a friction radius of 3 mm, and a temperature of room temperature (25 °C).

[0100] Friction coefficient test results are as follows Figure 5As shown, the DLC film obtained at a power of 150W ruptured after about 6 minutes of friction, while the films of other samples did not rupture completely during the 10-minute friction test. The friction coefficient of the 60NiTi substrate is approximately 0.5. After high-power pulse deposition of the DLC film on its surface, the friction coefficient of the samples decreased significantly. The friction coefficients of the samples with deposition powers of 100W, 150W, and 200W were 0.29, 0.17, and 0.19, respectively. The 150W sample had the lowest friction coefficient, which may be due to the high sp2 hybridization ratio in the sample of Example 2. Films with a high sp2 ratio of graphite type have better lubrication effects.

[0101] In summary, the high-power pulsed magnetron sputtering DLC ​​film of this invention exhibits a hardness of 6.01–7.18 GPa, an elastic modulus of 49.4–55.94 GPa, and an H / E ratio between 0.121 and 0.130. Currently reported hardnesses for 60NiTi alloys range from 56 to 62 HRC, elastic moduli are approximately 100 GPa, and H / E ratios range from 0.031 to 0.058. High-power pulsed magnetron sputtering of the DLC film on the surface of the 60NiTi alloy increases the H / E value by 2–4 times, significantly improving its wear resistance. Furthermore, the coefficient of friction of the 60NiTi alloy after stabilization is around 0.5, which is relatively high; after applying the high-power pulsed magnetron sputtering DLC ​​film, the coefficient of friction is reduced to around 0.2. The high-power pulsed magnetron sputtering DLC ​​film significantly reduces the coefficient of friction on the 60NiTi alloy surface, resulting in a substantial improvement in its wear resistance, providing a new approach for the development of aerospace bearing materials.

[0102] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for improving the wear resistance of 60NiTi alloy by using high-power pulsed magnetron sputtering of DLC film, comprising the following steps: Using Ti as the target material, a first high-power pulsed magnetron sputtering was performed on the surface of a 60NiTi substrate to obtain a 60NiTi substrate with a deposited Ti transition layer. A second high-power pulsed magnetron sputtering was performed on the surface of the 60NiTi substrate with a deposited Ti transition layer using a mixed gas of ethylene and high-purity argon as the working gas, to form a DLC film on the surface of the Ti transition layer. The parameters of the first high-power pulsed magnetron sputtering include: The working air pressure is 0.6~0.8 Pa; Set the frequency to 400~600 Hz; The pulse width is 50~115 μs; The power is 150~200 W; The working time is 10-15 minutes; During the second high-power pulsed magnetron sputtering, the argon flow rate is 90~100 ccm and the ethylene flow rate is 1.5~2.5 sccm; The parameters of the second high-power pulsed magnetron sputtering include: The working air pressure is 0.6~0.8 Pa; The operating frequency is 500~700 Hz; The sputtering power is 100~200 W; The target-base distance is 10~15 cm; The working time is 50~60 minutes.

2. The method according to claim 1, characterized in that, Before the first high-power pulsed magnetron sputtering, the 60NiTi substrate is further subjected to pretreatment, which includes the following steps: The 60NiTi substrate was ground, polished, and cleaned.

3. The method according to claim 1, characterized in that, The first high-power pulsed magnetron sputtering was performed in an argon atmosphere.

4. The method according to claim 1, characterized in that, The thickness of the Ti transition layer is 0.2~0.5 μm.

5. The method according to claim 1, characterized in that, During the second high-power pulsed magnetron sputtering, the 60NiTi substrate with the deposited Ti transition layer is fixed at the center of the sample stage and maintains its rotation.

6. The method according to claim 1, characterized in that, The total thickness of the Ti transition layer and the DLC film is 1.2~1.7 μm.

7. A 60NiTi alloy-DLC film composite material, obtained by treating a 60NiTi substrate using the method described in any one of claims 1 to 6; the 60NiTi alloy-DLC film composite material comprises a 60NiTi substrate, a Ti transition layer located on the surface of the 60NiTi substrate, and a DLC film layer located on the surface of the Ti transition layer.

Citation Information

Patent Citations

  • Cutter coating as well as preparation method and application thereof

    CN117568767A